Evolution of Haemophilia Care in Europe: 10 years of the principles of care - D. Noone; B. O’Mahony; F. Peyvandi; M. Makris; A. Bok (Orphanet Journal of Rare Diseases, 2020)
Abstract Introduction The European principles of care in haemophilia marked their first decade in 2018. These guiding principles were the beginning of the European Haemophilia Consortium (EHC) review of countries’ adherence to these principles in 2009, 2012, 2015 and 2018. The aim of this paper was to examine the implementation of the principles and how they have impacted the evolution of care in the last decade, as well as to identify remaining gaps and proposes future directions. Methods In 2018, the EHC distributed a survey to EHC national member organisations in English and Russian and encouraged them to discuss responses with local clinicians for accuracy. Data was also cross-referenced and validated for countries in earlier surveys using additional available resources. Results The 10-year-old European principles had a significant impact on the development of care for haemophilia and related bleeding disorders in Europe. They set objectives around which multi-stakeholder groups have established recommendations and specific steps for the progressive improvement of care for bleeding disorders. However, some have been promoted and implemented more than others. Conclusion Monitoring adherence to, and impact of, the European Principles of Care significantly assists in tracking developments and highlighting gaps. Countries’ inability to report consistent and coherent data remains a challenge and hinders both provision of treatment and care for patients as well as optimal national and European healthcare systems.